Attitudes of Undergraduate Medical Students towards the Persons with Mental Illness in a Medical College of Western Region of Nepal - Jalan, Rekha (Journal of Nepalgunj Medical College, 2018)
Background: The universality of harmful beliefs and subsequent negative attitude towards the persons with mental illness among medical students are the main obstacles facing the mentally ill people that further prevents them from seeking help and care for their mental health problems. Mental health education plays a significant role in changing medical students’ attitude towards persons with mental illness. Aim: The aim of this study was to assess undergraduate medical students’ attitude towards persons with mental illness and to compare their attitudes before and after mental health education. Materials and methods: A longitudinal prospective study was carried on final year MBBS students (N=68) from June, 2017 to November, 2017. Pretest- posttest design was adopted using Attitude Scale for Mental Illness (ASMI) before and after theory classes and clinical posting for mental health education. Results: Findings of present study revealed that these students were less stigmatized (6.44+1.93). Domain of restrictiveness improved (9.44+2.94 from 10.54+3.09) and benevolence increased significantly (t=2.440; P=0.017*) after mental health education and training. Overall attitude of the study population was found to have unhealthy attitude towards persons with mental illness since the mean scores on separatism, stereotyping, restrictiveness and pessimistic prediction subscales were elevated on ASMI. Conclusion: In conclusion, mental health education was found to be effective in changing the attitude of restrictiveness i.e., decreasing an uncertain view on the rights of people with mental illness and increasing kindness and sympathetic view to some extent among undergraduate medical students towards the persons with mental illness.